2004
DOI: 10.1037/0033-2909.130.3.512
|View full text |Cite
|
Sign up to set email alerts
|

Is the Promissory Note of Personality as Vulnerability to Depression in Default? Reply to Zuroff, Mongrain, and Santor (2004).

Abstract: In contrast to D. C. Zuroff, M. Mongrain, and D. A. Santor (2004), the current authors find the promissory note of dependency-sociotropy (DEP-SOC) and self-criticism-autonomy (SC-AUT) as a model of risk for depression to be in default. The authors propose reorganizing what has been cast as unitary effort into 3 distinct endeavors: a psychoanalytic clinical theory, development of a refined empirical model of risk for clinical depression, and research examining the effects of DEP-SOC and SC-AUT on interpersonal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(44 citation statements)
references
References 59 publications
0
43
0
1
Order By: Relevance
“…Further research is needed to investigate this suggestion. Furthermore, an important issue is whether elevated levels of dependency and self-criticism in the clinical samples may reflect state and/or scar effects of previous episodes of depression [Coyne et al, 2004]. Although studies have shown that both dependency and self-criticism are relatively stable personality dimensions [Luyten et al, 2005;Zuroff et al, 1999Zuroff et al, , 2004, with state effects accounting for only a minor proportion of variance in scores on the DEQ Dependency and Self-Criticism subscales, and evidence for the scar hypothesis is limited [Zuroff et al, 2004], some studies have had more mixed results [Klein et al, 2002].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further research is needed to investigate this suggestion. Furthermore, an important issue is whether elevated levels of dependency and self-criticism in the clinical samples may reflect state and/or scar effects of previous episodes of depression [Coyne et al, 2004]. Although studies have shown that both dependency and self-criticism are relatively stable personality dimensions [Luyten et al, 2005;Zuroff et al, 1999Zuroff et al, , 2004, with state effects accounting for only a minor proportion of variance in scores on the DEQ Dependency and Self-Criticism subscales, and evidence for the scar hypothesis is limited [Zuroff et al, 2004], some studies have had more mixed results [Klein et al, 2002].…”
Section: Discussionmentioning
confidence: 99%
“…Because the majority of these studies have involved normal subjects, however, the extent to which these findings generalize to severity of depression in patients with MDD remains unclear [Coyne et al, 2004;Enns et al, 2001]. In addition, the difference in association between dependency and self-criticism and severity of depression might depend on the measure of depression used.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Apesar da aceitação do QED, alguns investigadores têm apresentado algumas críticas ao instrumento, inclusivamente questionado a sua validade (e.g., Coyne & Whiffen, 1995;Coyne, Thompson, & Whiffen 2004;Desmet, Vanheule, & Verhaeghe, 2006;Lehman et al, 1997;Viglione, Philp, Clemmey, & Camenzuli, 1990). Uma das críticas que foi realizada tem a ver com o próprio sistema de cotação, demasiado complexo, e baseado em pesos factoriais, em que cada item entra na cotação dos diversos factores.…”
Section: Introductionunclassified
“…Nevertheless, some investigators have questioned its validity (e.g., Coyne, Thompson, & Whiffen, 2004;Coyne & Whiffen, 1995;Desmet, Vanheule, & Verhaeghe, 2006;Lehman et al, 1997;Viglione, Clemmey, & Camenzuli, 1990). First, the relative predictive utility of self-criticism versus dependency remains unclear.…”
Section: The Depressive Experiences Questionnairementioning
confidence: 99%